Production and resource utilization of flue gas desulfurized gypsum in China - A review. (1st November 2021) - Liu, Sen; Liu, Wei; Jiao, Fen; Qin, Wenqing; Yang, Congren
Abstract: Flue gas desulfurized gypsum (FGD gypsum), mainly originates from thermal power plants, smelters, and large-scale enterprise boilers. This article reviews the production in China and the latest beneficial utilizations of FGD gypsum. China is a large coal-consuming country and has always had serious SO2 emissions. Therefore, the Chinese government has implemented a large number of desulfurization measures since 2006. With continually increasing energy consumption and increasingly stringent environmental requirements, the production of FGD gypsum has exceeded 10 8 tons. The basic properties and the current beneficial applications of FGD gypsum are summarized here. The practical application of FGD gypsum in four fields—building materials, agriculture, material synthesis, and soil—and its impact on the environment, are analyzed. Finally, a new direction is proposed for the future utilization of FGD gypsum. Graphical abstract: Image 1 Highlights: Properties and production of FGD gypsum in China are given. Chinese government desulfurization measures during 2000–2019 are summarized. The application of FGD gypsum and its impact on the environment are analyzed. A possible closed-loop utilization of FGD gypsum is proposed.